The genetics of Autism Spectrum Disorders: a guide for clinicians - Heil, Karsten M.; Schaaf, Christian P. (Current psychiatry reports, 2013)
Recent advances in genetic testing technology have made chromosome microarray analysis (CMA) a first-tier clinical diagnostic test for Autism Spectrum Disorders (ASDs). Two main types of microarrays are available, single nucleotide polymorphism (SNP) arrays and array comparative genomic hybridization (aCGH), each with its own advantages and disadvantages in ASDs testing. Rare genetic variants, and copy number variants (CNVs) in particular, have been shown to play a major role in ASDs. More than 200 autism susceptibility genes have been identified to date, and complex patterns of inheritance, such as oligogenic heterozygosity, appear to contribute to the etiopathogenesis of ASDs. Incomplete penetrance and variable expressivity represent particular challenges in the interpretation of CMA testing of autistic individuals. This review aims to provide an overview of autism genetics for the practicing physician and gives hands-on advice on how to follow-up on abnormal CMA findings in individuals with neuropsychiatric disorders.
Published online: 13 December 2012
Gesehen am 08.10.2021